2014
DOI: 10.1039/c4ob00545g
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic enantioselective construction of multi-functionalized spiro oxindole dienes

Abstract: A diastereo- and enantio-selective domino Michael-cyclization-tautomerization reaction of isatylidene malononitriles with α,α-dicyanoalkenes catalyzed by a cinchona alkaloid-derived bifunctional thiourea catalyst has been developed. A series of multi-functionalized spiro oxindole diene derivatives have been obtained in good to excellent yields (up to 97%) with good to excellent enantioselectivities (up to 96%) as well as good diastereoselectivities (up to 7.9 : 1). In addition, an anomalous temperature effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 96 publications
0
29
0
Order By: Relevance
“…According to the literature [4][5][6][7][8][9][10][11][12] and our experiment, the possible mechanism was proposed in Scheme 3. A was formed from the Knoevenagel condensation reaction of cyclohexanone and malononitrile.…”
Section: Scheme 2 Synthesis Of 4a On Gram Scalementioning
confidence: 90%
See 1 more Smart Citation
“…According to the literature [4][5][6][7][8][9][10][11][12] and our experiment, the possible mechanism was proposed in Scheme 3. A was formed from the Knoevenagel condensation reaction of cyclohexanone and malononitrile.…”
Section: Scheme 2 Synthesis Of 4a On Gram Scalementioning
confidence: 90%
“…[4] Organic bases, such as pyrrolidine, [5a] morpholine, [5b] imidazole, [5c] ethanediamine [5d] and NEt 3 , [5e,5f] as efficient catalysts for the synthesis of ortho-aminocarbonitriles de-rivatives have also been reported. In addition, zinc titanate nanopowder, [6] glucose-containing imidazolium salt, [7] saccharine, [8] triethylamine acetate (TEAA), [8] benzyltriethylammonium chloride (TEBAC), [9] Borax, [10] deep eutectic solvent [11] and cinchona alkaloid-derived bifunctional thiourea [12] have been used to promote the formation of ortho-aminocarbonitriles derivatives. Despite these developments, many of these methods still have limitations such as the use of commercially unavailable reactants or catalysts, involve relatively harsh conditions, go through multistep procedures, require specific solvents or workup precausions.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, such nucleophiles were extensively employed in asymmetric vinylogous reactions to access many significant chiral frameworks ,. For example, Wang and co‐workers reported that hydroquinine‐derived thiourea 67 could catalyze the reaction of 2‐cyclohexylidene malononitrile 64 and 2‐cyclopentylidene malononitrile 65 with isatylidene malononitriles 66 (Scheme ) . After the reaction experienced a domino vinylogous Michael‐cyclization‐tautomerization process, spiro oxindole dienes 68 and 69 were obtained in moderate to excellent enantioselectivites and poor to moderate diastereoselectivities.…”
Section: Direct Strategiesmentioning
confidence: 99%
“…The process yielded highly functionalized spiro-oxindole dienes 106 . The products were obtained in good to excellent yields (up to 97%) and enantioselectivities (up to 96%), but the diastereoselectivities were moderate (up to 7.9:1) ( Scheme 34 ) [ 53 ].…”
Section: Reviewmentioning
confidence: 99%